English women's voices, 1540-1700 - Otten, Charlotte F. (Florida International University Press, 1992)
"This collection resurrects an extraordinary array of women's writings from the mid-sixteenth through the seventeenth centuries. The focus of English Women Voices is not on females writing "literature" but on the actual lives of women, as described in their own words. The work is organized around such themes as health care, religion, politics, marriage, and education, an approach that cuts across genre and chronology and shows the significant contributions of women to their culture. Recorded in diaries, letters, sermons, pamphlets, formal petitions, health manuals, trial records, biographies, and autobiographies, the words escape from the past, as vital as current events. The opening section, "Women Testifying to Abuse," candidly describes aspects of female life that even today often remain secret. The final section, which records the voices of women preaching, will touch a nerve in women who still struggle for the right to be heard from the pulpit. Each section begins with an introduction that situates the writing in its historical context; each introduction has a suggested-readings list that opens the subject to further research." "Burdened by what were perceived as the metaphysical, moral, and physiological limitations of women, the authors of these writings were enjoined to silence. Though sometimes published in their own day, the works were subsequently interred in research libraries or on microfilm. Vibrant with personal concerns, these voices will pierce the consciousness of twentieth-century readers and contribute to scholarship in literature and history courses and in all aspects of gender studies."--Jacket